a + b + c = λ for reals a , b , c . We define t n = c y c ∑ a 2 n + 1 for n ∈ N . Further it's given that t 1 = λ 3 . Find the value of λ if n = 1 ∑ ∞ t n = 6 1 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
How can there be no loss in generality when assumed that a + b = 0 ? Please explain !
Log in to reply
Because he's saying that the same logic can be applied for b + c = 0 and a + c = 0
When I read your solution my whole hard work on this question went in vain. This is not fair!
In front of your solution mine is just madness of millennium . I expanded the expression
Problem Loading...
Note Loading...
Set Loading...
t 1 = a 3 + b 3 + c 3 = ( a + b + c ) 3 .
Expanding and subtracting a 3 + b 3 + c 3 from both sides of the equation, then factorising gives the key result: 3 ( a + b ) ( b + c ) ( c + a ) = 0
Thus one of ( a + b ) , ( b + c ) , ( c + a ) = 0 .
WLOG let a + b = 0 then t n = a 2 n + 1 + ( − a ) 2 n + 1 + c 2 n + 1 = c 2 n + 1 .
Let the infinite sum be S. Summing all t i gives 1 − c 2 c 3 . This is by the formula for geometric progressions. Another condition for c appears, which is that the absolute value of c <1. But solving the equation S = 6 1 gives only one real solution c = 0 . 5 ⟹ a + b + c = 0 . 5 .